Strategi Inspektorat Daerah Dalam Penyelenggaraan Pengawasan Internal di Lingkungan Organisasi Perangkat Daerah Provinsi Jawa Barat - Muhammad Aldi Rahmandika (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2025)
This study aims to analyze the strategy of the Regional Inspectorate in implementing internal supervision within the Regional Apparatus Organizations of West Java Province. The research employs a descriptive qualitative approach using Kooten’s strategic framework, which consists of organizational strategy, program strategy, resource support strategy, and institutional strategy. Data were collected through observation, interviews, and documentation involving eight informants from the Regional Inspectorate and related regional agencies. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the internal supervision strategy implemented by the Regional Inspectorate of West Java Province has been relatively effective, particularly in terms of organizational, program, and institutional strategies. However, weaknesses remain in the resource support strategy, especially regarding the availability and optimization of human resources and supporting facilities. This condition affects the overall effectiveness of internal supervision, particularly in supporting the achievement of the Integrity Assessment Survey in the future. Therefore, strengthening resource support is necessary to enhance the sustainability and effectiveness of internal supervision.